Evaluation and additional recommendations for preparing a whole blood control material - Fink, Nilda E.; Fernández Alberti, Alejandra; Crispini, Isabel; Cabutti, Norberto V.; Mazziotta, Daniel (Revista de Saúde Pública, 1998)
OBJECTIVE: The assessment of an easy to prepare and low cost control material for Hematology, available for manual and automated methods. MATERIAL AND METHOD: Aliquots of stabilized whole blood were prepared by partial fixation with aldehydes; the stability at different temperatures (4. 20 and 37 °C) during periods of up to 8-9 weeks and aliquot variability with both methods were controlled. RESULTS: Aliquot variability with automated methods at day 1, expressed as CV% (coefficient of variation) was: white blood cells (WBC) 2.7, red blood cells (RBC) 0.7, hemoglobin (Hb) 0.6, hematocrit (Hct) 0.7, mean cell volume (MCV) 0.3, mean cell hemoglobin (MCH) 0.6, mean cell hemoglobin concentration (MCHC) 0.7, and platelets (PLT) 4.6. The CV (coefficient of variation) percentages obtained with manual methods in one of the batches were: WBC 23, Hct 2.8, Hb 4.5, MCHC 5.9, PLT 41. Samples stored at 4ºC and 20ºC showed good stability, only a very low initial hemolysis being observed, whereas those stored at 37ºC deteriobed a rapidly (metahemoglobin formation, aggregation of WBC and platelets, as well as alteration of erythrocyte indexes). CONCLUSIONS: It was confirmed that, as long as there is no exposure to high temperatures during distribution, this material is stable, allowing assessment, both esternal and internal, for control purposes, with acceptable reproductivity, both for manual and auttomatic methods.